(untitled) (Anclajes, 2021)
This works examines how the dramaturgical creative act varies according to the reality of the artist in exile, whether at home or abroad, in the context of Argentina’s last dictatorship (1976-1983). Our corpus examines three playwrights in exile at the time in Spain (Bortnik, Gambaro and Raznovich) and the works of two artists who considered the topic of exile while remaining in Argentina (Gris de ausencia by Cossa and Lejana tierra prometida by Halac). In turn, this allows us to consider an ontological perspective of theatre and uphold the vitality of contact between Argentina, Spain and Italy during this time.